2006
DOI: 10.1578/am.32.2.2006.202
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Variables Affecting the Residence of Spinner Dolphins (<I>Stenella longirostris</I>) in a Bay of Tahiti (French Polynesia)

Abstract: The spinner dolphin (Stenella longirostris) is the most common among 16 species in the Society Islands (French Polynesia). They are observed yearround during daytime in sheltered bays or within lagoons. From 1995 to 2002, we studied spinner dolphins from a shore site in Baie des Pêcheurs, a bay on the west coast of Tahiti, performing 1,033 sighting sessions with binoculars. Presence, position, and school size were noted, as well as various behavioral and environmental variables. Human presence also was recorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 5 publications
2
13
0
Order By: Relevance
“…Habitat features of spinner dolphin around Mayotte are slightly different from those in other areas. In French Polynesia, Hawaii, and the Maldivian atolls, these dolphins enter atolls, sheltered bays and lagoons through reef channels in the morning and leave in the afternoon to feed overnight (Würsig et al 1994, Anderson 2005, Gannier and Petiau 2006. Around Mayotte, the spinner dolphins under study generally inhabited the outer-reef slope, within a greater depth range than has been previously reported (Würsig et al 1994, Gannier andPetiau 2006).…”
Section: Discussionmentioning
confidence: 79%
“…Habitat features of spinner dolphin around Mayotte are slightly different from those in other areas. In French Polynesia, Hawaii, and the Maldivian atolls, these dolphins enter atolls, sheltered bays and lagoons through reef channels in the morning and leave in the afternoon to feed overnight (Würsig et al 1994, Anderson 2005, Gannier and Petiau 2006. Around Mayotte, the spinner dolphins under study generally inhabited the outer-reef slope, within a greater depth range than has been previously reported (Würsig et al 1994, Gannier andPetiau 2006).…”
Section: Discussionmentioning
confidence: 79%
“…In the waters around Hawai'i, USA, island-associated spinner dolphins spend their nights foraging intensively offshore for approximately eleven hours each night and return to shallow areas during the day, particularly from late morning to early afternoon (Norris and Dohl, 1980;Benoit-Bird and Au, 2003;Benoit-Bird, 2004;Tyne et al, 2015). This daily behavioral pattern has also been observed in Fiji (Cribb et al, 2012), French Polynesia (Gannier and Petiau, 2006;Oremus et al, 2007), Egypt (Notarbartolo-di-Sciara et al, 2009), Mauritius (Webster et al, 2015), Brazil (Silva-Jr et al, 2005), and both the northwestern (Karczmarski et al, 2005;Andrews et al, 2010) and main Hawaiian Islands (Norris and Dohl, 1980;Wursig et al, 1994;Tyne et al, 2015) This rigid daily behavioral schedule of spinner dolphins is a driver of an industry focused on human-dolphin interactions in Hawai'i (Heenehan et al, 2014). The rapid increase of human-dolphin interactions and the demands of intensive cooperative night-time foraging have led to concern about the effects of these interactions, particularly the consistent disruption of dolphin rest (NMFS and NOAA, 2006;Courbis and Timmel, 2009;Tyne et al, 2015).…”
Section: Introductionmentioning
confidence: 79%
“…Recent habitat modelling studies conducted in Hawaii, also demonstrated that spinner dolphins favor flat sandy seabeds, close to the 100m isobath (Thorne et al, 2012, Tyne et al, 2015. Although few specific substrate data analyses have been undertaken, other studies in Hawaii (Norris et al, 1994), in Hawaii's Midway Atoll (Karczmarski et al, 2005), in Tahiti (Gannier and Petiau, 2006) and in Mauritius (Webster, 2011), also reported the occurrence of spinner dolphin sightings in white-sand environments. This marked preference is consistent with the hypothesis first proposed by Norris et al (1994) that the species favors white sandy bays to improve visual detection of predators, especially during resting periods.…”
Section: Spinner Dolphin Habitatmentioning
confidence: 96%
“…This preference for flat areas at the outer part of the shelf, close to open waters, might be related to the species' ecological needs. Spinner dolphins generally use sheltered coastal or reef-associated habitat during the morning for resting and socializing and travels to deeper waters later in the afternoon where it forages at night (De Lima Silva and Da Silva, 2009;Gannier and Petiau, 2006;Kiszka et al, 2011;Lammers, 2004;Norris et al, 1994;Notarbartolo-Di-Sciara et al, 2008;Thorne et al, 2012;Tyne et al, 2015). It has been hypothesis that selecting resting habitat at close proximity to deep waters could be a strategy to reduce travelling time and energy costs during transit between oceanic and coastal habitats (Norris et al, 1994;Thorne et al, 2012;Tyne et al, 2015).…”
Section: Spinner Dolphin Habitatmentioning
confidence: 99%
See 1 more Smart Citation